تقييم التجربة الجزائرية في مجال دعم وترقية المؤسسات الصغيرة والمتوسطة - جديدي, روضة; طواهر, محمد التوهامي (جامعة الوادي - University of Eloued, 2013)
تشكل المؤسسات الصغيرة والمتوسطة في الجزائر عنصرا فاعلا في عملية التنمية،لهذا عملت الدولة منذ سنوات على تسخير كل طاقاتها المادية والبشرية والتقنية لدعم وترقية هذا القطاع،فتعددت بذلك البرامج واختلفت السياسات وتنوعت الهيئات كل ذلك من اجل مساعدة هذه المؤسسات على النمو والتطور والاستمرارية في ظل المنافسة الشرسة التي تعرفها السوق الجزائرية خاصة بعد توقيع اتفاقية الشراكة مع الاتحاد الاوروبي. والآن وبعد مسيرة اكثر من عشر سنوات،حان الوقت لتقييم هذه التجربة لرصد المكاسب المحققة والكشف عن النقائص التي حالت دون نمو وتطور المؤسسات الصغيرة والمتوسطة. ومن هذا المنطلق جاءت هذه الورقة البحثية تحت عنوان "تقييم التجربة الجزائرية في مجال دعم وترقية المؤسسات الصغيرة والمتوسطة" Small and medium-sized SME enterprises in ALGERIA are the vital element in the development process. In recent years, the State has deployed diversified actions and is implementing means to support, encourage and improve this sector. For this, policies and programs are adopted and public bodies created to that end to help these companies develop and better face the fierce competition that the ALGERIAN market is experiencing, particularly after the signature of the partnership agreement with the 'European Union. Now, after 10 years, it is time to evaluate this experience to identify on one side the benefits recorded and on the other hand the shortcomings and constraints that have prevented the growth, development and evolution of small and medium-sized enterprises. From this point of view is developed this presentation entitled "Evaluation of the Algerian experience in the field of support and upgrading of small and medium enterprises"
مقال
Keywords: المؤسسات الصغيرة والمتوسطة،مشاتل المؤسسات،حاضنات الاعمال، مراكز التسهيل،المقاولة من الباطن،تأهيل المؤسسات الصغيرة والمتوسطة; enterprises, business incubators, incubator, facilitation centers, outsourcing, rehabilitation of small and medium enterprises